Characterization of water from the Chavimochic Drinking Water Treatment Plant for compliance with Drinking Water Quality Regulation (SCIÉNDO INGENIUM, 2026)
The aum of this study was to identify contaminants present in the surface water entering the Chavimochic Drinking Water Treatment Plant from the Santa River intake and to evaluate the quality of the drinking water distributed in the province of Trujillo. The research was applied in nature, with a non-experimental and cross-sectional design. Samples were collected at different points during the dry and wet seasons, and physicochemical, inorganic, and microbiological parameters were analyzed using standardized laboratory methods. The results were compared with the Maximum Permissible Limits established by current national regulations. The findings showed that surface water exhibited high levels of turbidity, total coliforms and heavy metals such as arsenic, iron, and manganese, with greater incidence during the wet season. In drinking water, most parameters complied with regulatory standards; however, values close to or exceeding the limits were identified at certain points, requiring greater control of hardness, sulfates, nitrates, arsenic, and total coliforms. It is concluded that, although the treatment process generally ensures the quality of distributed water, factors associated with seasonal variability and system conditions may affect its potability.
Keywords: Water quality; surface water; drinking water; water treatment plant; heavy metals